2022
DOI: 10.3389/fpls.2022.1000093
|View full text |Cite
|
Sign up to set email alerts
|

Early detection of pine wilt disease tree candidates using time-series of spectral signatures

Abstract: Pine wilt disease (PWD), caused by pine wood nematode (PWN), poses a tremendous threat to global pine forests because it can result in rapid and widespread infestations within months, leading to large-scale tree mortality. Therefore, the implementation of preventive measures relies on early detection of PWD. Unmanned aerial vehicle (UAV)-based hyperspectral images (HSI) can detect tree-level changes and are thus an effective tool for forest change detection. However, previous studies mainly used single-date UA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 56 publications
(85 reference statements)
0
3
0
Order By: Relevance
“…Since PSND varies with vegetation chlorophyll content, it can be used to estimate the chlorophyll content or to assess vegetation senescence [35,36]. Run Yu et al showed that REP and PSRI could distinguish infected red pine from healthy red pine after 30 days [37]. The ability of PSRI to detect pine wilt disease was also verified by Dewei Wu et al [38].…”
Section: Discussionmentioning
confidence: 96%
“…Since PSND varies with vegetation chlorophyll content, it can be used to estimate the chlorophyll content or to assess vegetation senescence [35,36]. Run Yu et al showed that REP and PSRI could distinguish infected red pine from healthy red pine after 30 days [37]. The ability of PSRI to detect pine wilt disease was also verified by Dewei Wu et al [38].…”
Section: Discussionmentioning
confidence: 96%
“…However, there were instances where data from one sensor complemented the processing of data from other sensors in order to identify disease symptoms. Examples include the study of Yu et al [114], in which hyperspectral, RGB, and LiDAR sensors were involved. Data from the LiDAR sensor (i.e., digital elevation model data) were used during the pre-processing step of hyperspectral data.…”
Section: Sensors Used For the Detection And Monitoring Of Plant Diseasesmentioning
confidence: 99%
“…Data from the LiDAR sensor (i.e., digital elevation model data) were used during the pre-processing step of hyperspectral data. The identification of pine wilt disease symptoms was then conducted based on information retrieved from the hyperspectral and RGB sensors [114].…”
Section: Sensors Used For the Detection And Monitoring Of Plant Diseasesmentioning
confidence: 99%